Steam city kits: A project for primary schools that combines storytelling, hands-on activities, and physical computing - Raposo, Rui; Vairinhos, Mario (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper presents a comprehensive description of the STEAM City Kit project, an exploratory project developed according to a Framework for Innovation process model, as part of the Aveiro Tech City project, and designed for primary school students and teachers. The kit, which consists of 2 children’s stories with hands-on activities, an Arduino, and a wide range of sensors, was developed by a transdisciplinary team from the University of Aveiro and distributed to over 30 schools in the municipality of Aveiro, Portugal.